A Concise Enantioselective Synthesis of (S)-Preclamol via Asymmetric Catalytic Negishi Cross-Coupling Reaction - Zhou, Yun; Liu, Chunxiao; Wang, Lifeng; Han, Leng; Hou, Shicong; Bian, Qinghua; Zhong, Jiangchun (Synlett, 2019)
A novel, concise, and efficient enantioselective synthesis of (S)-preclamol (87% ee, 51% total yield) has been developed. The key steps of this synthetic approach included cobalt-catalyzed asymmetric catalytic cross-coupling of α-bromo ester with arylzinc and the reduction of chiral ester to diol with a tertiary carbon atom. Moreover, it was demonstrated that our enantioselective Negishi cross-coupling was a powerful tool to construct stereogenic benzylmethyl center in chiral drugs on a gram scale.
Keywords: (S)-preclamol; enantioselective Negishi cross-coupling; cobalt; asymmetric synthesis; chiral drug